(untitled) (Journal of Special Education and Rehabilitation, 2013)
COST project entitled ESSEA (Enhancing the Scientific Study of Early Autism) (2010-2014) is aimed to establish an interdisciplinary scientific European network to improve the detection of the earliest signs of autism, as well as to combine techniques from cognitive neuroscience with those from clinical sciences in order to establish practice guidelines on early identification and intervention of autism. The Macedonian team that actively participates in this project is composed of four participants: Acad. N. Pop-Jordanova, S. Markovska-Simoska PhD T. Zorcec, PhD and Prof. V. Trajkovski. The latest activity in this project was to obtain information about the usual early treatment in each country. For this aim, a questionnaire concerning the early treatment procedures used in each country have been translated and distributed to parents of children, younger than 6 years, with diagnosis ASD. Responses from 16 European countries, including Macedonia were obtained. I find it interesting to announce to our colleagues some of the obtained results. The questionnaire was distributed online in the period of 1. 5 month, in the autumn of 2012, through parents’ organizations, or by direct contact with parents of autistic children. From 16 countries, 2438 respondents filled in the questionnaire. Only 1681 (83%) of the questionnaires that were complete were included in the analysis.